Understanding the Experience of Hospital Pharmacists with the Effectiveness, Safety, Adverse Drug Reaction Reporting and Interchangeability of Biopharmaceutical Medicines - Ali Azeez Al-Jumaili; Hiba Leith Fahmi (College of Pharmacy University of Baghdad, 2022)
The study objectives were to 1) explore the real-world experience of hospital pharmacists with the differences in effectiveness safety, and interchangeability between biosimilar medicines and their reference biological counterparts, 2) reveal pharmacist recommendations to enhance the safety of biopharmaceutical medicines in public hospitals. The study has a mixed-method design where the core component was qualitative (interviews) and the supplemental component was quantitative (adverse drug reaction, ADR, reports). This qualitative component included semi-structured (mostly face-to-face) interviews involving hospital pharmacists from different hospitals with experience with biological or biosimilar medicines. The interviews were conducted from Nov 2020 through Feb 2021. Thematic analyses were used to analyze qualitative data generated from the interviews. The study sample included 25 pharmacists from ten governmental hospitals in Baghdad, Iraq. The pharmacists were 21 women and 4 men. Because most pharmacists had a short experience with biosimilar medications, they were unsure about their effectiveness and safety. Most pharmacists preferred reference biological over biosimilar medicines because of their effectiveness.  However, they believed that initial prescribing and switching between a reference and counterpart biosimilar rely on their availability. The pharmacists tended to underreport biopharmaceutical ADRs. The non-sustainable supply of the same biopharmaceutical medicines in public hospitals negatively impacted pharmacist evaluation of the effectiveness and safety of biosimilar medicines. Both pharmacist interviews and the Iraqi Pharmacovigilance Center (IqPhvC) data showed under-reporting of biopharmaceutical ADRs. Medicine procurement in healthcare settings should focus on sustainably securing high-quality biopharmaceuticals rather than looking only at costs to enhance patient clinical outcomes.  Providing pharmacist training, electronic reporting, promoting documentation, and following up with patients is pivotal to prevent, monitor and treat their ADRs.